Fabrication of Natural Fibre Reinforced Polymer Composite by Hand Lay-Up Process - Dhruv Kant Rahi; Himanshu Mishra; Sunil Kumar Tiwari; Sangharsh Kumar Singh; Pushkar Sharma (International Journal of Mechanical Dynamics and Systems Analysis, 2025)
The recent development in technologies has increased the usage of non-renewable resources during pro- duction due to remarkable properties. However, it has been a threat and unable to be replenished once used. In addition to this, natural fibre strengthens in a more significant way and it’s widely applicable in polymer composites materials. Furthermore, the use of plant fibres in polymer composites is due to its low cost and significant properties. Additionally, using natural fibers results in a lighter composite compared to those made with synthetic fibers. As a result, the massive demand for natural fibre composites commercially in the industrial sector for a safe environment. However, the development has many drawbacks and critical issues. The review focuses on various kinds of plant fibre polymer-Composite, along with its characteristics and applications. Therefore, in this paper, authors prepared Natural Fibre Reinforced Polymer Composite by Hand Lay-Up Process. Further, the tensile tests have been performed on this composite by using universal testing machine. This paper has also been summarized the chemical, mechanical, and physical properties of plant fibre and its reinforced polymer composites techniques. The shapes of specimens have been taken as (Length 34 mm, Width 24 mm, Thickness 4 mm). After that the average yield point of the workpiece has been found that 18.28 MPa.
Keywords: Epoxy resin; Jute fibers; Mild steel plates; Tensile Test; hand lay-up process